Mdm2 and p53 Expression in Radiation-Induced Sarcomas of the Head and Neck: Comparison with De Novo Sarcomas - Song, Min Jeong; Song, Joon Seon; Roh, Jong-Lyel; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon; Kim, Sung Bae; Lee, Sang-wook; Cho, Kyung-Ja (Journal of pathology and translational medicine, 2014)
The pathogenesis of radiation-induced sarcomas (RISs) is not well known. In RIS, TP53 mutations are frequent, but little is known about Mdm2-p53 interaction, which is a recent therapeutic target of sarcomas. We studied the immunohistochemical expression of Mdm2 and p53 of 8 RISs. The intervals between radiation therapy and diagnosis of secondary sarcomas ranged from 3 to 17 years. Mdm2 expression was more common in de novo sarcomas than RISs (75% vs 37.5%), and p53 expression was more common in RISs than in de novo cases (75% vs 37.5%). While half of the RISs were Mdm2(-)/p53(+), none of de novo cases showed such combination; while half of de novo sarcomas were Mdm2(+)/p53(-), which are a candidate group of Mdm2 inhibitors, only 1 RIS showed such a combination. Variable immunoprofiles observed in both groups did not correlate with tumor types, except that all of 2 myxofibrosarcomas were Mdm2(+)/p53(+). In conclusion, we speculated that both radiation-induced and de novo sarcomagenesis are not due to a unique genetic mechanism. Mdm2-expression without p53 overexpression in 1 case of RIS decreases the future possibility of applying Mdm2 inhibitors on a subset of these difficult tumors.